2019
DOI: 10.1002/ppul.24375
|View full text |Cite
|
Sign up to set email alerts
|

Lung function in school‐aged congenital diaphragmatic hernia patients; a longitudinal evaluation

Abstract: Objective Children with congenital diaphragmatic hernia (CDH) are at risk for pulmonary morbidity. Data on longitudinal evaluation of lung function in CDH are scarce. We hypothesized that CDH patients would have impaired lung function that worsens over time. We evaluated lung function and its determinants at ages 8 and 12 years. Methods Dynamic and static lung volumes, and diffusion capacity were measured. Extracorporeal membrane oxygenation (ECMO) treatment, the standardized European neonatal treatment protoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 34 publications
(89 reference statements)
1
14
0
Order By: Relevance
“…high ratio FEV1/peak flow) or restrictive pattern, with less frequent typical obstructive pattern (low FEV1/FVC), 25,26 especially for children with tracheobronchial fistula. 27 As previously observed in children with AO, 16 Previous studies have shown the impact of high neonatal respiratory morbidity on the QoL scores of children with CDH. 8,9,13 As in our study, Sheikh et al also observed lower scores in parents of children with a history of oxygen therapy need at 30 days of life.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…high ratio FEV1/peak flow) or restrictive pattern, with less frequent typical obstructive pattern (low FEV1/FVC), 25,26 especially for children with tracheobronchial fistula. 27 As previously observed in children with AO, 16 Previous studies have shown the impact of high neonatal respiratory morbidity on the QoL scores of children with CDH. 8,9,13 As in our study, Sheikh et al also observed lower scores in parents of children with a history of oxygen therapy need at 30 days of life.…”
Section: Discussionmentioning
confidence: 69%
“…Those results are consistent with the description of abnormal lung function parameters after CDH repair, which may worsen over time, showing that this affection is a complex developmental lung disease 1,4,24 . On the other hand, children with OA usually have a history of barky cough and a lung function profile of central airway obstruction (low peak expiratory flow; high ratio FEV1/peak flow) or restrictive pattern, with less frequent typical obstructive pattern (low FEV1/FVC), 25,26 especially for children with tracheobronchial fistula 27 …”
Section: Discussionmentioning
confidence: 99%
“…For this study, we selected children who completed a Pediatric Quality of Life Inventory (PedsQL, a PROM for HS) and/or Dutch-Child-AZL-TNO-Quality-of-Life (DUX-25, a PROM for QoL) questionnaire during follow-up assessments at eight years of age. Standardized assessments of health and daily functioning were performed as standard of care using previously described instruments and methods [ 11 , 12 , 13 , 14 ]. Although our follow-up protocol was subject to changes in regular care throughout the study period, evaluation methods were considered interchangeable and the same outcomes were measured over the years.…”
Section: Methodsmentioning
confidence: 99%
“…The second paper reported on 113 pulmonary function test (PFT) results performed at 8 and 12 years of age by 76 children born with CDH between 1999 and 2009. 9 Mean forced expiratory volume in one second (FEV 1 ) and forced expiratory flow (FEF 25%-75% ) declined between the 8-and 12-year measures, suggesting worsening obstruction on average. Mean static lung volumes were within normal limits and stable, while mean K CO was below normal but stable across the two time points.…”
Section: Anatomic Lung Airway and Vascular Malformationsmentioning
confidence: 99%
“…Lower exercise capacity was associated with longer initial hospital stay and lower diffusion capacity for carbon monoxide corrected for alveolar volume (K CO ). The second paper reported on 113 pulmonary function test (PFT) results performed at 8 and 12 years of age by 76 children born with CDH between 1999 and 2009 9 . Mean forced expiratory volume in one second (FEV 1 ) and forced expiratory flow (FEF 25%–75% ) declined between the 8‐ and 12‐year measures, suggesting worsening obstruction on average.…”
Section: Introductionmentioning
confidence: 99%